Methodology for avionics integration optimisation - Radaei, Mohammad (Cranfield University, 2020)
Every state-of-art aircraft has a complex distributed systems of avionics Line Replaceable Units/Modules (LRUs/LRMs), networked by several data buses. These LRUs are becoming more complex because of the increasing number of new avionics functions need to be integrated in an avionics LRU. The evolution of avionics data buses and architectures have moved from distributed analogue and federated architecture to digital Integrated Modular Avionics (IMA). IMA architecture allows suppliers to develop their own LRUs/LRMs capable of specific features that can then be offered to Original Equipment Manufacturers (OEMs) as Commercial-Off-The-Shelf (COTS) products. In the meantime, the aerospace industry has been investigating new solutions to develop smaller, lighter and more capable avionics LRUs to be integrated into avionics architecture. Moreover, the complexity of the overall avionics architecture and its impact on cable length, weight, power consumption, reliability and maintainability of avionics systems encouraged manufacturers to incorporate efficient avionics architectures in their aircraft design process. However, manual design cannot concurrently fulfil the complexity and interconnectivity of system requirements and optimality. Thus, developing computer-aided design (CAD), Model Based System Engineering (MBSE) tools and mathematical modelling for optimisation of IMA architecture has become an active research area in avionics systems integration. In this thesis, a general method and tool are developed for optimisation of avionics architecture and improving its operational capability. The tool has three main parts including a database of avionics LRUs, mathematical modelling of the architectures and optimisation algorithms. The developed avionics database includes avionics LRUs with their technical specifications and operational capabilities for each avionics function. A MCDM method, SAW, is used to quantify and rank each avionics LRU’s operational capability. Based on the existing avionics LRUs in the database and aircraft level avionics requirements two avionics architectures are proposed i.e. AFCS architecture (SSA) and avionics architecture (LSA). The proposed avionics architectures are then modelled using mathematical programming. Further, the allocation of avionics LRUs to avionics architecture and mapping the avionics LRUs to their installation locations are defined as an assignment problem in Integer Programming (IP) format. The defined avionics architecture optimisation problem is to optimise avionics architecture in terms of mass, volume, power consumption, MTBF and operational capability. The problems are solved as both single-objective and multi-objective optimisation using the branch-and-bound algorithm, weighted sum method and Particle Swarm Optimisation (PSO) algorithm. Finally, the tool provides a semi-automatic optimisation of avionics architecture. This helps avionics system architects to investigate and evaluate various architectures in the early stage of design from an LRU perspective. It can also be used to upgrade a legacy avionics architecture.
Keywords: Avionics Architecture; Optimisation; LRU; PSO; Integer Programming; MCDM; SAW; Database